The balance of autocrine VEGF-A and VEGF-C determines podocyte survival - Müller-Deile, Janina; Worthmann, Kirstin; Saleem, Moin; Tossidou, Irini; Haller, Hermann; Schiffer, Mario (American Journal of Physiology-Renal Physiology, 2009)
Podocytes are an important component of the glomerular filtration barrier and are the major source of vascular endothelial growth factor (VEGF) in the glomerulus. The role of VEGF for the phenotype of the glomerular endothelium has been intensely studied; however, the direct effects of autocrine VEGF on the podocyte are largely unknown. In this study we characterized the expression of VEGF isoforms and VEGF receptors in cultured human podocytes and examined direct effects on cell signaling and apoptosis after stimulation with exogenous VEGF or ablation of autocrine VEGF. We identified VEGF-A and VEGF-C as the dominant isoforms in human podocytes and showed that autocrine levels of both are important for the intracellular activation of antiapoptotic phosphoinositol 3-kinase/AKT and suppression of the proapoptotic p38MAPK via VEGFR-2. We demonstrated that ablation of VEGF-A or VEGF-C as well as treatment with bevacizumab or a VEGFR-2/-3 tyrosine kinase inhibitor led to reduced podocyte survival. In contrast, ablation of VEGF-B had no effect on podocyte survival. Treatment with exogenous VEGF-C reversed the effect of VEGF-A neutralization, and exogenous VEGF-A abrogated the effect of VEGF-C ablation in human podocytes. Our results underline the importance of autocrine VEGF for podocyte survival and indicate the delicate balance of VEGF-A and VEGF-C to influence progression of glomerular diseases. Copyright © 2009 the American Physiological Society.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Apoptosis; Cell survival